GROWTH OF SEAWEED Gracilaria verrucosa CULTURED ON DIFFERENT INITIAL WEIGHT WITH LONGLINE METHODS IN KARIMUNJAWA WATERS - TITIK SUSILOWATI; DICKY HARWANTO; CHONDRORESMI BANOR FAWWAZ; ALFABETIAN HARJUNO CONDRO HADITOMO; SARJITO SARJITO (Fakultas Biologi | Universitas Jenderal Soedirman, 2019)
One factor that can optimize seaweed production is determining the initial weight of planting. However, planting seaweed in open waters is very vulnerable to aggregation from herbivorous fish. This study aims to determine the best initial weight for the growth of G. verrucosa, which is cultivated in net cage by the longline method. Net cages, made of nylon, are applied as protection for G. verrucosa from aggregation of herbivorous fish. This research was conducted in Karimunjawa waters, Jepara Regency, Central Java, for 42 days. The experimental design used was Randomized Block Design (RBD), with three treatments and four replications each. The treatment was different initial planting weights of 25, 50, and 75 g. The observed variables included culture techniques, relative growth rates, specific growth rates, and water quality. The analysis showed that the different initial weight was very significant (P <0.01) on the growth of G. verrucosa. Treatment with an initial weight of 25 g gave the best relative growth rate (2.07±0.25%.d-1), and the best specific growth rate (1.48±0.13%.d-1). Furthermore, this study was able to prove that the use of a net planting cage on a seaweed hanger can avoid aggregation of herbivorous fish, which is indicated by the growth of G. verrucosa.